Indek Saprobik Komunitas dalam menentukan Tingkat Pencemaran di Perairan Laut antara Muara Sungai Benu dan Pulau Betet, Kabupaten Banyuasin, Propinsi Sumatera Selatan - Efendi Parlindungan Sagala (UNIVERSITAS SRIWIJAYA, 2011)
Index saprobic of plankton community was been analysis acording to research results about composition dan abundance the species of plankton have been carried out to water samples from sea waters between Benu River Estuary and Betet Island, December 2002 several years ago, 2002. According to the observation and researching in laboratory can be found 39 species of plankton organism consist of 28 species were phytoplankton and 11 species were zooplankton. There were ten grups of taxonomic categories which can be found in these study namely Cyanophyceae, Chlorophyceae, Desmidiaceae, Bacillariophyceae, Flagellata, Rhizopoda, Copepoda, Decapoda, Pelecypoda and Pisces. The abundance of plankton community were 25 individuals/liter (seawaters between Benu River and Betet Island) upto 127 individuals/liter (seawaters around Betet Island).The aim of calculating of plankton community saprobic index useful for determinate the levels of pollution levels in waters ecosystem. The results of research point out that ies in fact that plankton community saprobic index for five studies location between +1,09 upto +1,60. That of numeral results means the levels of pollution in around of study was moderate upto very slight with few organic and inorganic substances worked in phase of meso/oligosaprobic upto oligo/mesosaprobic. The lower of saprobic index 1,09 was in Estuary of Benu River and between Benu River and Betet Island. The moderate of saprobic index was the sea end of Betet Island Estuary and Estuary of Betet Island in Tanjung Pring with each results 1,28 and 1,37. The results of that four above consist of the moderate level pollution with the load of few organic and inorganic substances and into meso/oligosaprobic phase. The high of saprobic indeces and the best in these study was at the sea of Betet island, namely 1,60 that means very slight and few organic and inorganic substances and worked in oligo/mesosaprobic phase. Keywords:Saprobic Index, Plankton Community, Pollution ABSTRAK Indeks saprobik komunitas plankton dianalisis berdasarkan hasil pengamatan komposisi dan kelimpahan jenis-jenis plankton telah dilakukan terhadap contoh air yang diambil dari perairan laut antara muara Sungai Benu dan Pulau Betet, Desember, 2002. Dari pengamatan tersebut diperoleh 39 spesies plankton yang termasuk dalam 28 spesies fitoplankton dan 11 spesies zooplankton. Secara keseluruhan termasuk ke dalam 10 kategori taksonomi (Cyanophyceae, Chlorophyceae, Desmidiaceae, Bacillariophyceae, Flagellata, Rhizopoda, Copepoda, Decapoda, Pelecypoda dan Pisces). Kelimpahan komunitas plankton berkisar dari 25 individu/liter (laut antara S. Benu dan Pulau Betet) hingga 127 individu/liter (Laut di Pulau Betet).